The indirect effects of food insecurity on obesogenic environments - Allen, Jeffrey (Frontiers in Public Health, 2023)
Introduction: The Centers for Disease Control and Prevention (CDC) estimates 39.8 % of United States (US) residents are obese (Centers for Disease Control and Prevention (CDC), 2018). This study examined obesity-related factors at the county-level to determine the indirect effects on physical inactivity, insufficient sleep duration, income inequality, food insecurity, on obesity rates. Methodology: Using the 2018 Robert Wood Johnson Foundation (RWJF) County Health Rankings data set, a multiple regression analysis was conducted to measure the percentage of the obesity rate explained by physical inactivity, insufficient sleep duration, food insecurity, and income inequality. The indirect relationships between obesity-related variables and obesity were measured and illustrated through a path analysis model. Results: This study found the combination of independent variables explained 53% of the obesity rates in the US, R2 = .53, p < .001, two-tailed. This study also found that food insecurity has both a direct and indirect effect on obesity, physical inactivity, and insufficient sleep duration. Physical inactivity has a direct and indirect effect on obesity and a direct effect on insufficient sleep duration. Insufficient sleep duration has a direct effect on obesity. Conclusion: This analysis found that food insecurity indirectly impacts an obesogenic environment and drives county-level BMI averages. The dataset used for analysis predates the COVID-19 pandemic but presents the effect of food insecurity during a normative year. The findings, though interesting, provide an opportunity for future research. Keywords: food insecurity, obesity, physical inactivity, insufficient sleep, public health, health inequities